Study of the most prevalent neoplasms of the female reproductive system in a city in southeastern Goiás over a 26-year period (Research, Society and Development, 2025)
Objective: Given the scarce data and studies focused on this pathology in the municipality of Catalão-GO, this study aims to analyze the epidemiology of the most prevalent neoplasms, characterizing their location, age group, race, and sex. Methods: This is a descriptive and retrospective epidemiological study of a quantitative nature. The epidemiological data were obtained from the database of the Department of Informatics of the Brazilian Unified Health System (DATASUS). Results: In general, neoplasms affecting the female reproductive system have increased over the years analyzed. A higher prevalence of uterine leiomyoma was observed, followed by malignant neoplasms of the breast and cervix. Conclusion: The progressive increase in cases of neoplasms during the observed period may be related to the historical and socioeconomic context, as well as various risk factors present in the studied location.